Thinking small further? South Africa's company law reform and its German counterpart: perspectives for SMMEs - Baumann, Jan (Centre for Law and Society, 2026)
Every economy has its flagships that can be seen from afar. They fly the flags of Standard Bank, MTN, Vodacom, Deutsche Bank, Mercedes and BMW and are often the pride of the nation – or at least the pride of stock analysts. In their wake flow, another powerful armada – the thousands of small- and medium-sized entrepreneurial vessels – often used to sail below political radar level. But in the past few decades a paradigm shift towards a more entrepreneurial-friendly environment took place. In line with the realisation of the developmental assistance community that large-scale poverty reduction could only be achieved from within the economy,1 many policy makers realised the potential of small entrepreneurship. The slogan “thinks small first” quickly gathered momentum. And even though this valuable insight was picked up earlier in developing economies, such as the South Africa of the 1980s,2 it is now influencing the economic agenda around the world. Even the European Union felt the urge to focus more on the “think small first” approach. Günter Verheugen, former Vice President of the Commission of the European Union responsible for enterprise and industry policy is sure that “[e]ntrepreneurs and entrepreneurship are of enormous importance for our societies. Today and even more so tomorrow small and medium sized enterprises will provide for professional education and employment opportunities. Caring about SMEs means therefore caring about present and future jobs [...].”3 In 2006 micro, very small and small businesses accounted for 27 – 34 % of South Africa's total GDP,4 an impressive figure. But more importantly, those enterprises employed 56 % of all employees – with small businesses employing an impressive 21 % of all South African employees.